2017
DOI: 10.1002/2017jc013340
|View full text |Cite
|
Sign up to set email alerts
|

Satellite Altimetry and Current‐Meter Velocities in the Malvinas Current at 41°S: Comparisons and Modes of Variations

Abstract: Three year long current‐meter arrays were deployed in the Malvinas Current at 41°S below a satellite altimeter track at about 10 years intervals. Surface geostrophic velocities (SGV) derived from satellite altimetric data are compared with the in situ velocities at the upper current meter (∼300 m). Multisatellite gridded SGV compare better with in situ observations than along‐track SGV. In spite of the proximity of the moorings to the complex Brazil‐Malvinas Confluence (BMC) region, satellite SGV are significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
68
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(96 citation statements)
references
References 26 publications
(34 reference statements)
8
68
1
Order By: Relevance
“…Satellite altimeter‐derived geostrophic velocities are significantly correlated with 20 day low‐pass filtered current meter observations and corroborate the weak and strong regimes reported here (Ferrari et al, ). Ferrari et al () showed that the first two modes of variability explain up to 41% of the variance of sea‐level anomaly around the mooring location.…”
Section: Discussion and Summarysupporting
confidence: 88%
See 4 more Smart Citations
“…Satellite altimeter‐derived geostrophic velocities are significantly correlated with 20 day low‐pass filtered current meter observations and corroborate the weak and strong regimes reported here (Ferrari et al, ). Ferrari et al () showed that the first two modes of variability explain up to 41% of the variance of sea‐level anomaly around the mooring location.…”
Section: Discussion and Summarysupporting
confidence: 88%
“…Mesoscale process is probably at the origin of the deepening of the water masses during the weak Malvinas period as suggested by Maamaatuaiahutapu et al () to explain the presence of SAMW at a depth of 800 m north of 38°S. In turn, eddy kinetic energy mesoscale process is stronger during the weak Malvinas period (Ferrari et al, ) and thus intrusions of subtropical waters associated with intense mesoscale variability may favor the deepening of the water masses.…”
Section: Discussion and Summarymentioning
confidence: 85%
See 3 more Smart Citations